Modeling Ca2+-Bound Troponin in Excitation Contraction Coupling - Zot, Henry G.; Hasbun, Javier E. (Frontiers in Physiology, 2016)
To explain disparate decay rates of cytosolic Ca2+ and structural changes in the thin filaments during a twitch, we model the time course of Ca2+ bound troponin (Tn) resulting from the free Ca2+ transient of fast skeletal muscle. In fibers stretched beyond overlap, the decay of Ca2+ as measured by a change in fluo 3 fluorescence is significantly slower than the intensity decay of the meridional 1/38.5 nm-1 reflection of Tn; this is not simply explained by considering only the Ca2+ binding properties of Tn alone (Matsuo, T., Iwamoto, H., and Yagi, N. (2010). Biophys. J. 99, 193-200). We apply a comprehensive model that includes the known Ca2+ binding properties of Tn in the context of the thin filament with and without cycling crossbridges. Calculations based on the model predict that the transient of Ca2+ bound Tn correlates with either the fluo 3 time course in muscle with overlapping thin and thick filaments or the intensity of the meridional 1/38.5 nm-1 reflection in overstretched muscle. Hence, cycling crossbridges delay the dissociation of Ca2+ from Tn. Correlation with the fluo 3 fluorescence change is not causal given that the transient of Ca2+ bound Tn depends on sarcomere length, whereas the fluo-3 fluorescence change does not. Transient positions of tropomyosin calculated from the time course of Ca2+ bound Tn are in reasonable agreement with the transient of measured perturbations of the Tn repeat in overlap and non-overlap muscle preparations.